Efficient and improved method for the Biginelli reaction using solid superacid (sulphated SnO2) - Bhosale, R. S.; Hashmi, A. M.; Zubaidha, P. K.; Dongare, Mohan K. (Heterocyclic Communications, 2005)
One-pot synthesis of 3,4-dihydropyrimidin-2(1H)-one (DHPM) has been effected efficiently by coupling of the three components, aldehyde, ethyl acetoacetate and urea/thiourea in the presence of solid Superacid (sulphated SnO2). The method presented herein is attractive with respect to yield, reaction time, workup procedure and reusable catalyst.
Keywords: Biginelli; DHPM; sulphated SnO2